Product obsolescence: Design and market dynamics - Ribeiro, Pedro Henrique Lopes; Rezende, Edson Carpintero; Franco, Juliana Rocha (DAT Journal, 2021)
This article begins with a characterization of the different types of product obsolescence to demonstrate that it is not only an internal issue of the objects, but an internal issue crisscrossed by social and economic factors. Obsolescence is understood within the dynamics of project management, but also through contemporary forms of economic organization, especially production through global value chains. At the end of the text, two examples of companies’ strategies (Baratza and Flair) operating in the coffee equipment market were analyzed based on the elements presented throughout the article. The paper concluded that although there are practices that can be adopted, there are particularities according to the sector in which the companies operate that have considerable weight in the effectiveness of the measures adopted to reduce product obsolescence.